Pemberdayaan UMKM Melalui Legalitas Usaha di Desa Dongko Kecamatan Dongko - Windy Juli Astuti Ningtyas; Shamara Qanita; Lusia Ervi Oktaviarika; Mukhammad Ilham Aprilian; Wiwin Yulianingsih (Universitas Warmadewa, 2022)
After the economic crisis in 1997-1998, the economy in Indonesia began to increase due to the existence of the Micro, Small and Medium Enterprises (MSMEs) group which had been used as a group to develop their potential to natural potential. One of them is the development of economy in Indonesia has been widely run by the people of Dongko Village through 3 (three) business groups, namely the Women's Cooperative (KOPWAN)